Efektivitas Katalis Zeolit Alam Ende pada Pirolisis Polietilena dari Sampah Plastik - Bani, Gregorio Antonny (Jurnal Teknik Kimia USU, 2023)
The high amount of plastic waste in landfills will pollute the environment. Direct combustion releases pollutants into the air, and recycling is only possible in small quantities. One method to overcome this problem is pyrolysis. However, pyrolysis requires a catalyst such as zeolite to accelerate the reaction rate, lower the activation energy, and improve the basic properties of the pyrolysis liquid. This study aims to characterize the activated natural zeolite Ende and determine the effect of the catalyst from the activated natural Ende zeolite on the activation energy, as well as the quality of the liquid resulting from the pyrolysis. Based on the research results, the activation process could change the degree of crystallinity became 36.63%, the surface area became 74.57 m2/g, the average radius became 20,21 Ã…, the pore volume became 72.34 cm3/g, and the number of acid sites became 4.342 NH3/g zeolite. Ende's active natural zeolite catalyst in the polyethylene pyrolysis process from plastic waste reduced the activation energy to 4,371.1 cal/mol in treating 0.10% catalyst composition from 1 kg of plastic. Increasing the temperature and catalyst improves the quality of pyrolysis oil, but the composition of the catalyst ratio is 0.10% of 1 kg of plastic.